PROSES ELECTROPOLISHING ALUMINIUM 7075 YANG DITAMBAHKAN SKANDIUM DENGAN VARIASI POTENSIAL LISTRIK DAN WAKTU ELECTROPOLISHING - Sean Filbert, Bryan
Electropolish is a material polishing process using electrochemical principles in accordance with Faraday's law which aims to improve the final surface quality of the material. This process involves immersing the workpiece in an electrolyte solution and applying controlled electric potential and current, which can dissolve the surface of the material so that the surface of the workpiece becomes smooth. The research carried out focused on obtaining the electropolish range of aluminum 7075 with scandium added and obtaining the effect of electric potential and electropolish time on the morphology and surface roughness value of the material. The electrical potential range of the test specimen electropolishing process is obtained from linear sweep voltammetry measurements on the potentiostat. Then an electropolishing process was carried out on each test specimen with variations in time and electrical potential. The electropolish results were observed by a stereo microscope and an optical microscope to obtain the electropolish surface morphology results. Then the specimen is rough tested to determine the magnitude of the reduction in roughness value that occurs in the specimen. The research results show that the increase in electric potential and electropolishing time on 7075 aluminum material is directly proportional to the surface quality. However, in 7075 aluminum alloy with scandium added, increasing the electric potential and electropolish time causes the surface quality to decrease with increased roughness values and pitting corrosion observed on the surface.